Consumer's awareness towards Islamic banking: The case of Kota Kinabalu / Nur Azreeni Farhana Amir - Amir, Nur Azreeni Farhana (2013)
The purpose of conducting this research is to fulfill the syllabus of MKT662 in order for the university to award the bachelor degree. The concept of Islamic banking was formally in Malaysia in 1983. The majority of population is Muslim so religious factor plays fundamental role in the awareness of Islamic banking because it has a sense of interest free banking and each type of transaction is strictly prohibited whose subject matter is Harram according to the doctrines to Islamic banks. Islamic banks also have many opportunities and potential customers in these areas and it is consistently growing.